Holograms and Avatars for political persuasion - Ricoy Casas, Rosa María (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper analyzes the use of holograms and avatars in communication and political marketing. It explores its origin, types, extent, examples and real cases of its use in various areas; technical difficulties at the current stage of development; its application as a technique of persuasion in the political scenario, and some legal and ethical problems. It also reflects on how 5G and the creation and use of metaverses will be spaces that will consolidate these tools.